An unusual [4 + 4] cycloadduct from an o-quinodimethane: Characterisation and computational studies. Issue 1 (4th January 2018) - Ramabhadran, Raghunath O.; Abdul Rahman, Mohamed Husaini bin; Collier, Steven J.; Storr, Richard C.; Bates, Roderick W.
Abstract: Trapping of a pyrimidinone-derived o -quinodimethane with tetraphenylcyclopentadienone gives a mixture of the [4 + 2] and formal [4 + 4] adducts. Computational studies show that the latter arises by a sequence of [4 + 2] cycloaddition, homolysis, radical recombination to a spiro-tetrahydrofuran and Claisen rearrangement under the thermolytic conditions. Graphical abstract: